Cover Feature: [All]‐S, S‐dioxide Oligo‐Thienylenevinylenes: Synthesis and Structural/Electronic Shapes from Their Molecular Force Fields (Chem. Eur. J. 2/2019). Issue 2 (10th December 2018) - Aharon, Cheryl; Guijarro, Fernando G.; Medina Rivero, Samara; Ramírez, Francisco J.; Caballero, Rubén; Casado, Juan; Langa, Fernando; Rozen, Shlomo
Abstract : Making more electron‐deficient oligothiophene vinylenes (OTVs) by selective oxidation of the sulfur atoms converts them into significantly more π‐conjugated molecules, with enhanced inter‐ring/exocyclic π‐conjugation and, concomitantly, with enhanced optical features. This unique oxidation of OTVs leaves the surrounding electron‐rich olefins intact. A comparison of these [all]‐S, S‐dioxide oligothienylene‐vinylenes with their parent oligothienylene‐vinylenes and also with oligothiophenes has been carried out. More information can be found in the Communication by J. Casado, F. Langa, S. Rozen, et al. onpage 464 .